‘Tax exceptionalism': a South African tax law perspective - Tembe, Fezile (Department of Commercial Law, 2025)
This study examines the manner in which South African courts approach the interpretation of fiscal legislation – by asking whether, courts are developing some sort of exceptional approach in statutory interpretation when it comes to tax law? This is the crux of the concept ‘tax exceptionalism', the misconception that tax law is fundamentally different and therefore should not be governed by the same rule of statutory interpretation that generally apply in the interpretation of all other legislation. For the first time this study examines this concept from South African perspective. In the discussion, the study makes an analysis to the recent court decisions namely Pienaar Bros, NWK and Brummeria cases, and looks at the approaches employed in the interpretation of these cases as tax matters. It further asks whether the same conclusions would have been reached if the above cases were not tax cases. Having considered the above decisions, the conclusion reached is that even after more than two decades of the Constitutional dispensation ‘tax exceptionalism' still exists in South Africa, and evidenced by the constant creation of new rules that apply exceptionally in the interpretation of fiscal legislation and not in all other legislations.